Shaping the future: principles for policy recommendations for responsible innovation in virtual worlds - Cork, Alicia G.; Richardson, Mike; Lukosch, Heide K.; Khamis, Mohamed; Katins, Christopher; Krauß, Veronika; Ruffin, Lauren; Papazoglakis, Sarah; Sanchez, Victoria; Pan, Xueni; Proulx, Michael J.; Stanton Fraser, Danaë (Frontiers in Virtual Reality, 2025)
Extended Reality (XR) technologies are beginning to enter the mainstream and have the potential to change the way humans interact with computers on a global scale. As with all powerful tools, XR not only has the potential for enormous good, but also brings in a new set of challenges for policy to guide its innovation and development. This paper draws on a wide range of expertise from academia, research and development, and industry to collectively provide guiding principles for XR policy. The authors began discussions and developed a framework at a workshop at ACM SIGCHI 2024 and the ideas presented here are the result of debate, discussion, refinement, and offer next steps for the development of pervasive XR. We present three main principles for XR policy: Trust, Agency, and Inclusivity, along with a cross-cutting theme of Future-Proofing. Each principle is broken down and we offer example implementations. This paper aims to build upon previous work and efforts for fair and equitable XR for all, and further dialogue towards tangible changes in policy to help guide responsible innovation in virtual worlds.